Effect of Priming Treatment to Enhance Seed Quality of Sorghum - NISHA; SS JAKHAR; AXAY BHUKER; SATPAL (Seed Research, 2026)
With a view to find out the effect of priming on germination and seedling vigour on sorghum (Sorghumbicolor L.) seeds, experiments were conducted during Kharif 2018 in Seed Technology Laboratory, Department ofSeed Science & Technology, CCS Haryana Agricultural University, Hisar (Haryana), India.The seed of two foragesorghum variety (HC 136 and HJ 541) were evaluated under five priming treatments viz. T1: Untreated (control),T2: Hydration -dehydration (6 h,T3:Hydration – dehydration (6 h) + 0.25 % thiram treatment.T4: Hydration with GA3(50 ppm for 6 h),T5:Hydration with sodium molybdate (500 ppm for 6 h) in complete randomized block design andreplicated thrice.Maximum germination percentage and seedling length were observed when seeds primedwithT4:Hydration with GA3 (50 ppm for 6 h), followed by Hydration – dehydration + 0.25 % Thiram treatment(T3)similar trend was also observed in all parameters. Among the treatments T1 Untreated (control) recordedminimum germination %, Seedling Length, seedling dry weight, Seed Vigour index and dehydrogenase activity.Among all the priming treatments T4 Hydration with GA3 (50 ppm for 6 h) was found to be the best primingtreatment. Moreover, priming treatments have more pronounced effect on HJ541 maintained highest qualityparameters followed than HC136 of sorghum seeds.